The Influence of Personality and Family Environment on Interest in Entrepreneurship Faculty of Economic State University of Jakarta - Adriansyah, Muhammad Yusuf; Zulaihati, Sri; Susanti, Santi (Luxury: Landscape of Business Administration, 2023)
This study aims to: 1) determine the influence of personality on the interest in entrepreneurship; (2) regarding the influence of the family environment on the interest in entrepreneurship; and (3) the influence of personality and family environment knowledge on the interest in entrepreneurship. The population in this study were 222 students of the Faculty of Economics, Jakarta State University, class of 2019. In this research instrument researchers used quantitative methods, as many as 144 respondents. data collection using a questionnaire. Data is processed using SPSS. The results of the research instrument show that personality and family environment have a significant effect on interest in entrepreneurship. Based on the results of research that has been done, this is also influenced by personality and family environment as previously explained. Based on the results of research conducted by researchers on variable X1, it appears that the lowest percentage of personality indicators is shown by openness. Based on the research conducted, this happens because the personality of a person or student is not always open or open minded towards the entrepreneurial field. Based on the results of research conducted by researchers on family environment variables, it appears that the lowest percentage of indicators is shown in the way parents educate. This indicates that the way parents educate their children to enter the world of entrepreneurship is still lacking. Based on the results of research conducted by researchers on family environment variables, it appears that the lowest percentage of indicators is shown in the way parents educate. This indicates that the way parents educate their children to enter the world of entrepreneurship is still lacking.